The Ideal Characteristics of Higher Education Music Institutes in 21st century Thailand - Thuntawech, Saya; Trakarnrung, Somchai (Malaysian Journal of Music, 2017)
In the 21st century, there are many factors affecting the survival of music institutes. In Thailand, music in higher education has been a part of the Thai educational system for more than 80 years. Sixty-eight higher education institutes are reported to provide music degree programmes. The objective of this study was to investigate the ideal characteristics of higher education music institutes in Thailand in the 21st century. Participants selected through purposive sampling included eleven administrators from higher education music institutes in Thailand. This is a design study that used a qualitative approach by collecting data through the in-depth interview method. The results showed that the characteristics of the ideal music institute in Thailand in the 21st century could be explained as having three main parts: 1) administration and management— this deals with four major issues including the philosophy of the institute, styles of the institute, administration strategies and finances; 2) curriculum and instruction—this is concerned with levels of the study, purpose of the programme, content, teaching styles, evaluation and assessment, music activities and services; and 3) resources that include buildings and environment, library and databases, and human resources.